Chondroitin Sulfate Immobilized on a Biomimetic Scaffold Modulates Inflammation While Driving Chondrogenesis. (24th March 2016) - Corradetti, Bruna; Taraballi, Francesca; Minardi, Silvia; Van Eps, Jeffrey; Cabrera, Fernando; Francis, Lewis W.; Gazze, Salvatore A.; Ferrari, Mauro; Weiner, Bradley K.; Tasciotti, Ennio
Abstract : This article proposes a chondroitin sulfate-based biomimetic scaffold that recapitulates the physicochemical features of the chondrogenic niche and retains the immunosuppressive potential of mesenchymal stem cells in vitro, either in response to a proinflammatory cytokine or in the presence of stimulated peripheral blood mononuclear cells. Abstract: : Costs associated with degenerative inflammatory conditions of articular cartilage are exponentially increasing in the aging population, and evidence shows a strong clinical need for innovative therapies. Stem cell-based therapies represent a promising strategy for the treatment of innumerable diseases. Their regenerative potential is undeniable, and it has been widely exploited in many tissue-engineering approaches, especially for bone and cartilage repair. Their immune-modulatory capacities in particular make stem cell-based therapeutics an attractive option for treating inflammatory diseases. However, because of their great plasticity, mesenchymal stem cells (MSCs) are susceptible to different external factors. Biomaterials capable of concurrently providing physical support to cells while acting as synthetic extracellular matrix have been established as a valuable strategy in cartilage repair. Here we propose a chondroitin sulfate-based biomimetic scaffold that recapitulates the physicochemical features of the chondrogenic niche and retains MSC immunosuppressive potential in vitro, either in response to a proinflammatory cytokine or in the presence of stimulated peripheral blood mononuclear cells. In both cases, a significant increase in the production of molecules associated with immunosuppression (nitric oxide and prostaglandins), as well as in the expression of their inducible enzymes ( iNos, Pges, Cox-2, and Tgf-β ). When implanted subcutaneously in rats, our scaffold revealed a reduced infiltration of leukocytes at 24 hours, which correlated with a greater upregulation of genes involved in inflammatory cell apoptotic processes. In support of its effective use in tissue-engineering applications of cartilage repair, the potential of the proposed platform to drive chondrogenic and osteogenic differentiation of MSC was also proven. Significance: Recently, increasing clinical evidence has highlighted the important role of proinflammatory mediators and infiltrating inflammatory cell populations inducing chronic inflammation and diseases in damaged cartilage. This work should be of broad interest because it proposes an implantable biomimetic material, which holds the promise for a variety of medical conditions that necessitate the functional restoration of damaged cartilage tissue (such as trauma, diseases, deformities, or cancer).